Does counseling affect parental postpartum depression? - Soheila Rabiepoor; Atefeh Yas (Hygeia Press di Corridori Marinella, 2018)
Introduction and objectives: During pregnancy and after childbirth, parents experience new roles and responsibilities, which may affect their mood and lead to postpartum depression. The present study examines the effects of counseling on postpartum depression in parents. Materials and methods: The study is a clinical trial on 76 couples from Urmia, Iran. The samples were chosen from week 34 of pregnancy to 6 months after childbirth and randomly assigned to control (38 couples) and intervention (38 couples) groups. The control group received routine care, while parents in the intervention group received routine care plus five counseling sessions. All the women and their spouse in the control and intervention groups were assessed with the Edinburgh Postpartum Depression Scale at the beginning of study, 2 and 6 months after childbirth. Descriptive statistics tests and t-test were used to extract the results. P-values less than 0.05 were considered significant. Findings: Mean Edinburgh depression score 2 months after childbirth was higher for control group mothers (10.18 ± 1.53) as compared with the intervention group (8.21 ± 1.43). This was statistically significant. The mean Edinburgh depression scores for fathers in the control and intervention groups were 6.92 ± 1.51 and 6.36 ± 1.42, respectively, but this difference was not statistically significant. Also, the mean Edinburgh depression scores 6 months after childbirth were found to be higher for the control group mothers (p = 0.001) and fathers (p = 0.019), and this was statistically significant. Conclusion: The results of this study showed that couple-based counseling significantly decreased depression scores of nulliparous women within 2-6 months after delivery. However, the interventions failed to have effects on fathers within 2 months after childbirth and only proved statistically effective after 6 months.